Exchange Transfusion in Neonatal Hyperbilirubinemia: Experience of A Tertiary Care Hospital in Dhaka (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Hyperbilirubinaemia is a benign condition in newborn babies in some infants may become severe, progressing to kernicterus with substantial risk of neonatal mortality and long-term neurodevelopmental impairments. Among many treatment options exchange transfusion (ET) is the standard method for treatment of severe hyperbilirubinemia.Objectives: To investigate the frequency of primary risk factors for neonatal hyperbilirubinemia leading to ET, to evaluate the complications and immediate outcome of ET.Methods: This was an observational cross sectional study conducted in Dr. MR Khan Shishu Hospital and ICH, Dhaka. Frequency of primary risk factors for severe neonatal hyperbilirubinemia leading to ET, characteristics of babies undergoing ET, complications and immediate outcome of ET were analyzed among the neonates admitted between January 2017 to February 2021.Results: Among 61 neonates 49.18% were male and 50.82% were female, 65.57% of neonates were term and 34.43% pre term. The mean gestational age was 37.00 ± 1.50 weeks and mean birth weight was 2619±50gm. The leading causes of jaundice requiring ET were sepsis 31.17%, ABO incompatibility 24.59%, Rh incompatibility 14.75%, PT LBW with sepsis 14.75%, Infant of diabetic mother (IDM) 6.55%, PT LBW 6.55%, and neonatal sepsis with Down syndrome with congenital hypothyroidism 1.63%. Twenty (32.79%) neonates presented with signs of Kernicterus. Seven neonates (35%) presented with lethargy/poor feeding or hypotonic posture, 4(20%) patients had opisthotonus posture/hypertonia, and 9(45%) had convulsion. Nineteen (31.14%) neonates had complications related to ET. The most frequent complication was bradycardia (16.34%), then Catheter block (9.83%), apnaea (6.55%), cardiac arrest (6.55%), hypothermia (4.92%), NEC after ET (1.64%). Immediate outcome was good in 72.13% patients with smooth recovery, 14.75% had neurological deficit and 1.64% died. Among 20 neonates who presented with signs of Kernicterus 35% patients discharged with good recovery, 45% had neurological deficit.Conclusion: The common causes of exchange transfusion in neonatal jaundice were sepsis, ABO incompatibility, PT LBW, and infants of diabetic mothers. Overall outcome was good few developed neurological deficit.DS (Child) H J 2022; 38(2): 89-95